Different expression of BRAFV600E, ALK and PD-L1 in melanoma in children and adolescents: a nationwide retrospective study in Finland in 1990-2014 - Rousi Emma K.; Koskivuo Ilkka O.; Juteau Susanna M.; Talve Lauri A.I.; Hernberg Micaela M.; Vihinen Pia P.; Kähäri Veli-Matti (TAYLOR & FRANCIS LTD, 2022)
Background Pediatric melanoma may have a different biological background and more favorable prognosis compared with melanoma in adults. The aim of this study was to investigate melanoma in children and adolescents in the Finnish population in terms of incidence, clinical course, treatment, prognosis and BRAFV600E-, ALK- and PD-L1-positivity of the primary tumors.
Materials and Methods Primary tumor samples and clinical records of all patients aged 0-19 years diagnosed with cutaneous melanoma in Finland in 1990-2014 were collected using the Finnish Cancer Registry database, Finnish hospitals and private pathology laboratories. BRAFV600E, ALK and PD-L1 were analyzed from 54 primary tumors and BRAFV600E from six metastasis samples.
Results A total of 122 patients diagnosed with cutaneous melanoma were retrieved from the Cancer Registry database. The primary tumor samples of 73 patients were obtained for the review, and 56 cases were included in the study. The incidence of pediatric melanoma increased from 0.2 to 1.0/100 000 during the period 1990-2014. Spitzoid melanoma was the most common subtype (66%). The 10-year cancer-specific survival (CSS) was 88.7% in all patients. The 10-year-CSS did not differ in SLNB-positive or -negative groups. BRAFV600E was positive in 48%, ALK in 9% and PD-L1 in 2% of the tumors. BRAFV600E mutation was associated with 83% of melanoma deaths. Conclusions Young melanoma patients had more favorable prognosis and a different staining profile for BRAFV600E, ALK, and PD-L1 in primary tumor than reported in adults. SLNB status was not an indicator for survival. BRAFV600E-positive patients have worse prognosis and could benefit from surveillance and treatment similarly to adults.